An International Clinical Study of Ability and Disability in Autism Spectrum Disorder Using the WHO-ICF Framework - Mahdi, S.; Albertowski, K.; Almodayfer, O.; Arsenopoulou, V.; Carucci, S.; Dias, J.; Khalil, M.; Knüppel, A.; Langmann, A.; Lauritsen, M.; da Cunha, G.; Uchiyama, T.; et al. (Springer New York LLC, 2018)
© 2018 The Author(s) This is the fourth international preparatory study designed to develop International Classification of Functioning, Disability and Health (ICF, and Children and Youth version, ICF-CY) Core Sets for Autism Spectrum Disorder (ASD). Examine functioning of individuals diagnosed with ASD as documented by the ICF-CY in a variety of clinical settings. A cross-sectional study was conducted, involving 11 units from 10 countries. Clinical investigators assessed functioning of 122 individuals with ASD using the ICF-CY checklist. In total, 139 ICF-CY categories were identified: 64 activities and participation, 40 body functions and 35 environmental factors. The study results reinforce the heterogeneity of ASD, as evidenced by the many functional and contextual domains impacting on ASD from a clinical perspective.